Gaps in cancer care in a multi-ethnic population in Sarawak, Borneo : A central referral centre study - Melissa Lim, Siaw Han; Voon, Pei Jye; Adibah, Ali; Fitri Suraya, Mohamad; Jong, Lin Lin; Chew, Lee Ping; Mohamad Adam, Bujang; Yolanda, Augustin; Cheng, Yuong Kang (PLOS ONE, 2024)
Background The state of Sarawak on the island of Borneo in East Malaysia, in working towards developing and strengthening cancer services through a holistic patient-centred approach, must focus on the comprehensive needs of cancer patients by taking into account the psychosocial, cultural and spiritual aspects of Sarawak’s multi-ethnic, multi-cultural population. Methods A 42-item survey questionnaire was developed and validated with a total of 443 patients. The perceived importance of information provided and level of patient satisfaction were assessed with a 5-point Likert scale in 10 domains (Diagnosis, Surgery, Radiotherapy, Systemic therapy, Clinical trials, Pain management, Treatment monitoring, Psychosocial support, Sexual care and fertility issues, and Financial support). A Spearman’s rank correlation test was applied to determine the correlation between response in both item and domain categories for perceived importance and satisfaction. Results Overall, patients were more satisfied with information related to cancer diagnosis, treatment and surgery but less satisfied with information pertaining to sexual aspects of care and family planning, psycho-social support and financial support. The majority of patients were satisfied with the level of treatment-related information received but preferred the information to be delivered in more easily comprehendible formats. Sexual aspects of care and family planning, psychosocial support and treatment monitoring post-discharge were perceived as important but seldom addressed by health care professionals due to lack of professional counsellors, social workers and clinical nurse specialists. Many patients face financial toxicity following a cancer diagnosis, particularly when diagnosed with advanced cancer requiring complex multi-modality treatment.